Breastfeeding Education Package And Successfully Of Early Breast-Feeding - Ina Handayani; Gilang Purnamasari (Jurnal Kesehatan Prima, 2020)
This study aims to analyze the effect of breastfeeding education packages for successful of early breastfeeding. This type of research was a quantitative study with a quasi-experimental design with a non-randomize Post-test Only Control Group Design. This research conducted at a health center in Bogor of months Juni until Agustus 2018. The number of samples of each group was 27 respondents to the sampling technique used unpaired numerical, analytical research samples. The media of education used booklets compiled by researchers from a variety of sources. The instrument used a questionnaire about successfully breastfeeding based on body position, emotion, anatomy, suckling, and time. Data were analyzed using the Mann-Whitney test. The median value of breastfeeding success in the intervention group was 26,  while in the control group, it was 22. Based on the results of the analysis found that there is an influence of breastfeeding education packages on the provision of preliminary results with a value of p 0.003 (p <0.05). Successfully of early breastfeeding in the intervention group were given breastfeeding education package is higher than the control group. Conclusion: The breastfeeding education package significantly affects the success of early breastfeeding. Lactation management education, especially about early breastfeeding and support from health workers, is expected for successfully breastfeeding mothers.